Periodical publications and their approach to the recent past: a look at "ADN Cultura" (Clepsidra - Interdisciplinary Journal of Memory Studies, 2024)
The article proposes an approach to the construction of memory narratives from the paradigm of the material turn. Considers the material dimensions of the book on the recent past, its circulation and instances of mediation. In this way, from an interdisciplinary perspective that crosses studies on book circulation, memory studies, and literary studies, adresses the reading of cultural supplements and instances of mediation, prioritization, and promotion of books about political violence. The mediation operations of the cultural supplement ADN cultura are taken as an example, and they are thought of from positions that, on the one hand, question the status of testimony, and on the other, redistribute voices from the social arc, to reconstruct the past from the paradigm of the complete memory.
Keywords: Periodicals, Material Turn, Recent Past, Cultural Journalism, Testimony, Dictatorship